The dynamic genome a Darwinian approach - Fontdevila, Antonio, 1941- (Oxford : Oxford University Press, 2011)
This title provides a synthetic, readable account of some widely debated evolutionary issues in the context of our growing understanding of functional genomics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Genomics; Genomes; Evolution (Biology)